Insects With Survival Kits for Desiccation Tolerance Under Extreme Water Deficits - Thorat, Leena; Nath, Bimalendu B. (Frontiers in Physiology, 2018)
The year 2002 marked the tercentenary of Antonie van Leeuwenhoek’s discovery of desiccation tolerance in animals. This remarkable phenomenon to sustain ‘life’ in the absence of water can be revived upon return of hydrating conditions. Today, coping with climate change-related factors, especially temperature-humidity imbalance, is a global challenge. Under such adverse circumstances, desiccation tolerance remains a prime mechanism of several plants and a few animals to escape the hostile consequences of fluctuating hydroperiodicity patterns in their habitats. Among small animals, insects have demonstrated impressive resilience to dehydration and thrive under physiological water deficits without compromising on revival and survival upon rehydration. The focus of this review is to compile research insights on insect desiccation tolerance, gathered over the past several decades from numerous laboratories worldwide working on different insect groups. We provide a comparative overview of species-specific behavioral changes, adjustments in physiological biochemistry and cellular and molecular mechanisms as few of the noteworthy desiccation-responsive survival kits in insects. Finally, we highlight the role of insects as potential mechanistic models in tracking global warming which will form the basis for translational research to mitigate periods of climatic uncertainty predicted for the future.